2021
DOI: 10.1021/acs.jpclett.1c00208
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–Liquid Phase Separation of Tau Protein Is Encoded at the Monomeric Level

Abstract: Liquid–liquid phase separation (LLPS) is involved in both physiological and pathological processes. The intrinsically disordered protein Tau and its K18 construct can undergo LLPS in a distinct temperature-dependent manner, and the LLPS of Tau protein can initiate Tau aggregation. However, the underlying mechanism driving Tau LLPS remains largely elusive. To understand the temperature-dependent LLPS behavior of Tau at the monomeric level, we explored the conformational ensemble of Tau at different temperatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 87 publications
(158 reference statements)
8
59
0
Order By: Relevance
“…The Tau43 domain in the solution NMR htau40 investigation has increased β‐sheet propensity, 13 also recent reports show β‐populated domains in different diseased Tau isoforms 57,58 . However, Tau43 structural ensemble, within currently simulated timescales, are intrinsically unstructured with transient structural propensity, in qualitative agreement with several studies, 11,28,34,59–61 where relatively compact, transiently structured, yet disordered conformations have been predicted for monomeric and oligomeric conformational ensembles of Tau isoforms. Together, these indicate the current monomeric conformational ensemble to be a relatively compact yet unstructured metastable state in the early aggregation process of Tau43, which will be further underscored with corresponding insights from structural parameters.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The Tau43 domain in the solution NMR htau40 investigation has increased β‐sheet propensity, 13 also recent reports show β‐populated domains in different diseased Tau isoforms 57,58 . However, Tau43 structural ensemble, within currently simulated timescales, are intrinsically unstructured with transient structural propensity, in qualitative agreement with several studies, 11,28,34,59–61 where relatively compact, transiently structured, yet disordered conformations have been predicted for monomeric and oligomeric conformational ensembles of Tau isoforms. Together, these indicate the current monomeric conformational ensemble to be a relatively compact yet unstructured metastable state in the early aggregation process of Tau43, which will be further underscored with corresponding insights from structural parameters.…”
Section: Resultssupporting
confidence: 80%
“…Also, PHF6 is found to be the most hydrophobic, and conformationally most extended, in spite of displaying least conformational fluctuations, due to plausibly being shielded by contiguous segments from aqueous environment (Supporting Information Figure SI 5, Figure SI 6; Figures 6 and 7). Recent computational studies on K18, have found the PHF6 to display enhanced beta‐probability at all temperatures, unlike most of the other aggregate‐prone segments 61 . Our results further underscore the mechanistic insights as well as importance of PHF6 in the early aggregation process of Tau43.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…S2 and S4A). Interestingly, a similar non-monotonic behavior with temperature has been described for tau protein condensates (Dong et al, 2021).…”
Section: Resultssupporting
confidence: 69%
“…The C-terminus contains a basic microtubule-binding domain (MTBD), which is predominantly positively charged, followed by a negatively charged terminal region. The electrostatic interactions between domains and tau’s IDP nature allow the formation of condensed liquid tau droplets, both in vitro and in vivo [ 47 , 48 , 49 , 50 , 51 ]. Tau interacts with nuclear components such as nucleoli and nuclear speckles, as well as with cytoplasmic bodies such as stress granules and P granules [ 52 , 53 , 54 , 55 , 56 , 57 ].…”
Section: Nuclear Tau Modifies the Chromatin Landscapementioning
confidence: 99%